Self-efficacy, test anxiety, and academic success: A longitudinal validation. (2017) - Roick, Julia; Ringeisen, Tobias
Highlights: Validating the structure of anxiety predictors by means of control-value theory. Confirms the role of self-efficacy for goal attainment as suggested by the theory of self-regulation. Longitudinal validation study integrating assumptions of both theories. Model integrating assumptions from both theories fits the data best. Abstract: Control-value theory (CVT) specifies a sequence of variables assumed to predict achievement-related emotions, and related performance. Similarly, Schwarzer's theory of self-regulation (TSR) suggests that self-efficacy influences all links in the above-mentioned sequence. A longitudinal validation that integrates assumptions from both theories remains pending. Hence, the current study used a longitudinal design to validate the structure of anxiety predictors, thereby examining whether self-efficacy is associated with each link of the chain. A total of 92 students completed questionnaires at different time points before and after an oral examination. Using structural equation modeling, five separate models were run with stepwise involvement of the direct effects of self-efficacy on the other variables. Findings supported the proposed structure of relationships with self-efficacy affecting all variables.